Sediment bacterial biogeography across reservoirs in the Hanjiang river basin, southern China: the predominant influence of eutrophication-induced carbon enrichment - Yang, Haokun; Xiong, Xueling; Tai, Yiping; Xiao, Li-Juan; He, Dan; Wu, Liqin; Zhou, Lijun; Ren, Lijuan; Wu, Qinglong L.; Han, Bo-Ping (Frontiers in Microbiology, 2025)
A fundamental goal of reservoir ecosystem management is to understand bacterial biogeographic patterns and the mechanisms shaping them at a regional scale. However, little is known about how eutrophication, a major water quality challenge in reservoirs, influences sediment bacterial biogeographic patterns in subtropical regions. In this study, sediment bacterial communities were sampled from 21 subtropical reservoirs in the Hanjiang river basin, southern China, and spanning trophic states from oligotrophic to eutrophic. Our findings demonstrated that eutrophication-driven changes in total carbon (TC) significantly shaped the regional biogeographic patterns of sediment bacterial communities, weakening the “distance-decay” relationships that typically link bacterial community similarity to geographical distance. TC content exceeding a threshold of 13.2 g·kg−1 resulted in substantial shifts in bacterial community structure. Specifically, high TC levels promoted the dominance of copiotrophic bacteria such as Syntrophales (Deltaproteobacteria), Clostridiaceae (Firmicutes), and VadinHA17 (Bacteroidetes), while oligotrophic taxa like Anaerolineaceae (Chloroflexi) and Nitrospirota were prevalent in low TC sediments. Additionally, higher TC content was associated with increased regional heterogeneity in bacterial community composition. Reservoirs with elevated TC levels exhibited more complex bacterial interaction networks, characterized by stronger niche segregation and higher competition compared to low TC networks. Overall, these findings underscore the pivotal role of sediment TC in shaping bacterial biogeography at a regional scale. They provide valuable insights for predicting ecosystem responses to eutrophication and offer guidance for mitigating the impacts of anthropogenic activities on freshwater ecosystems.